2022
DOI: 10.1021/acscatal.2c03043
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Energy Release in a Reversible Molecular Solar Thermal System

Abstract: Molecular solar thermal (MOST) systems open application fields for solar energy conversion as they combine conversion, storage, and release in one single molecule. For energy release, catalysts must be controllable, selective, and stable over many operation cycles. Here, we present a MOST/catalyst couple, which combines all these properties. We explore solar energy storage in a tailor-made MOST system (cyano-3-(3,4-dimethoxyphenyl)-norbornadiene/quadricyclane; NBD′/QC′) and the energy release heterogeneously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…This energy can be released as heat when needed, making these systems ideal for providing energy on demand. Known as MOlecular Solar Thermal (MOST) systems, [2][3][4][5] they hold significant potential for revolutionizing the way we generate and store energy. [22][23][24][25] To be used as MOST systems, molecules must possess several key features (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…This energy can be released as heat when needed, making these systems ideal for providing energy on demand. Known as MOlecular Solar Thermal (MOST) systems, [2][3][4][5] they hold significant potential for revolutionizing the way we generate and store energy. [22][23][24][25] To be used as MOST systems, molecules must possess several key features (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…In the electrochemical approach, the energy release is controlled directly by the applied potential. The energy release in a heterogeneously catalyzed process is controlled using flow reactors. , While the electrochemical energy release requires a catalytically inactive electrode material, heterogeneous catalysts must be catalytically highly active and selective . For E / Z -AZOs and HetABs, electrochemical triggering can be achieved via a reductive reaction pathway. , In a recent study, we demonstrated that the energy release of the heteroaryl­azobenzene 3-cyanophenyl­azothiophene can be triggered electrochemically with high cyclability …”
mentioning
confidence: 99%
“…In this geometry mass transport in the thin layer is decoupled from the bulk solution. , Details on the setup are described in our previous work . The experimental procedure used for all three surfaces is depicted in Figure a.…”
mentioning
confidence: 99%
See 2 more Smart Citations